Problems of Micro Finance Program in Nepal with References of Cooperative Limited - Dhakal, Chandra Prasad (Perspectives on Higher Education, 2024)
Microfinance is one of the self-help programs run in Nepal both bank and cooperative limited. After COVID-19 pandemic microfinance program run by cooperative organizations face the problem like loan deficit, misusing the loan, failure to balance the bad debt, face problems to maintain the financial discipline. In this context, this study analyzes the causes of the failure of cooperative in Nepal. Main objective of this study is to highlights the perceptions of stakeholder toward the ongoing problems of microfinance in the context of Nepal. Research question of this study focuses on why microfinance programs run by the cooperatives have been facing the problems in Nepal and what are the possible solutions of the problems that are facing by the cooperatives in the mobilization of microfinance. The study followed the qualitative survey research design and analyzed the perception of stakeholders and possible way of solving problems on the view of the participants. Five individuals were involved in this study and expressed their opinion on the basis of the issues. Conclusion of this study has been made on the basis of primary data that has collected from the field by using in-depth interview. Misusing the resources, neglect the principle of cooperatives, weak monitoring, political protection on financial crime are the major cases of creating problems on micro credit run by the cooperatives in Nepal.